Ferozsons urdu english dictionary (Ferozsons Lahore)
The "Ferozsons Urdu-English Dictionary" is a comprehensive reference that provides accurate translations and meanings of Urdu words into English, and vice versa, with detailed explanations for effective language comprehension.